Impacts of interactions between ADH1B and ALDH2 genotypes on alcohol flushing, alcohol reeking on the day after drinking, and age distribution in Japanese alcohol-dependent men. Issue 3 (April 2020) - Yokoyama, Akira; Yokoyama, Tetsuji; Matsui, Toshifumi; Mizukami, Takeshi; Kimura, Mitsuru; Matsushita, Sachio; Higuchi, Susumu; Maruyama, Katsuya
Abstract : Objective: This study sought to evaluate the impacts of interactions between the alcohol dehydrogenase-1B (rs1229984) genotype and the aldehyde dehydrogenase-2 (rs671) genotype on alcohol flushing, alcohol reeking on the day after drinking, and the age distribution in alcohol-dependent patients. Methods: The study subjects were 4107 Japanese alcohol-dependent men who underwent alcohol dehydrogenase-1B and aldehyde dehydrogenase-2 genotyping: 4051 patients were asked about their current or former tendency to experience facial flushing after drinking a glass of beer, and 969 patients were asked about whether they had ever been told that they reeked of alcohol more than 12 hours after they had stopped drinking. Results: Current, former, and never flushing were reported in 3.5, 14.9, and 81.5%, respectively, of the subject, and alcohol reeking after more than 12 hours in 36.1% of the subjects. The fast-metabolizing ADH1B*2 (+) genotype ( *1/*2 or *2/*2 ) and the inactive ALDH2*2 (+) genotype ( *1/*2 or *2/*2 ) affected the multivariate odds ratios for current or former flushing [odds ratio, 95% confidence interval = 2.27 (1.79–2.86) and 23.0 (18.6–28.5), respectively, vs. *2(−) genotype] and for alcohol reeking [0.39 (0.29–0.52) and 1.56 (1.09–2.25), respectively, vs. *2(−) genotype]. An age-dependent decrease in the ADH1B*2 (−) and ALDH2*2 (−) combination from 32.3% in the 30–39-year age group to 12.5% in the 70–79-year age group and an age-dependent increase in the ADH1B*2 (+) and ALDH2*2 (−) combination from 52.5% in the 30–39-year age group to 70.5% in the 70–79-year age group were observed ( P < 0.0001 for trend). The frequencies of the ADH1B*2 (−) and ALDH2*2 (+) combination (4.7–6.2%) and the ADH1B*2 (+) and ALDH2*2 (+) combination (8.9–12.0%) did not change markedly with increasing age. Conclusion: Interactions between the alcohol dehydrogenase-1B and aldehyde dehydrogenase-2 genotypes modified alcohol flushing, alcohol reeking on the day after drinking, and the age distribution. These findings support the protective roles of the ADH1B*2 (+) and ALDH2*2 (+) genotypes against the development of alcohol dependence.